2002
DOI: 10.1046/j.1440-1819.2002.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

The neurotic versus delusional subtype of taijin‐kyofu‐sho: Their DSM diagnoses

Abstract: The main purpose of the present study was to investigate the diagnostic concepts of taijin-kyofu-sho (TKS) and social phobia, by comparing the clinical diagnosis of TKS and the operational diagnosis of Diagnostic and Statistical Manual of Mental Disorders (3rd edition, revised; DSM-III-R). Three evaluators conducted semistructured interview for DSM-III-R (SCID axis I and II, the Japanese version) to 88 outpatients who visited Jikei University Daisan Hospital, Japan, over a period of 1 year, requesting Morita t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 5 publications
5
38
0
1
Order By: Relevance
“…Studies in non-clinical samples found moderate correlations between social anxiety and features of offensive TKS in healthy volunteers of nonAsian or Japanese descent in the US [Kleinknecht et al, 1994], students in the US and Japan [Kleinknecht et al, 1997], and students in Japan reporting interpersonal difficulties [Tarumi et al, 2004]. A clinical study reported that 65.8% of Japanese outpatients with clinically diagnosed TKS also met DSM-III-R criteria for SAD [Nakamura et al, 2002], although SAD was more common among TKS patients characterized by ''neurotic'' symptoms (81.5%) than among those with ''delusional'' symptoms (27.3%). Case reports that have described seven American patients with offensive TKS challenge the disorder's cultural exclusivity, suggesting that offensive TKS does occur, at least sporadically, outside the Far East [Clarvit et al, 1996;McNally et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in non-clinical samples found moderate correlations between social anxiety and features of offensive TKS in healthy volunteers of nonAsian or Japanese descent in the US [Kleinknecht et al, 1994], students in the US and Japan [Kleinknecht et al, 1997], and students in Japan reporting interpersonal difficulties [Tarumi et al, 2004]. A clinical study reported that 65.8% of Japanese outpatients with clinically diagnosed TKS also met DSM-III-R criteria for SAD [Nakamura et al, 2002], although SAD was more common among TKS patients characterized by ''neurotic'' symptoms (81.5%) than among those with ''delusional'' symptoms (27.3%). Case reports that have described seven American patients with offensive TKS challenge the disorder's cultural exclusivity, suggesting that offensive TKS does occur, at least sporadically, outside the Far East [Clarvit et al, 1996;McNally et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…TK is a concept related to SAD and BDD. The categories of fear or anxiety and avoidance behavior are components that are as important in the assessment of TK as in that of SAD [2,40]. In the BDD-YBOCS, distress, resistance, and interference are equally assessed by the 2 categories of obsession and compulsion.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen patients (1 inpatient and 14 outpatients; 9 men and 6 women, mean age 24.8 ± 6.6 years) who met the traditional diagnostic criteria for c-TK (table 1) [40] gave signed informed consent for videotaped interviews. None of the patients had other comorbid psychiatric disorders (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…TK, however, has traditionally been divided into two categories in Japan, namely tension subtype and conviction subtype (Kasahara, 2005;Nakamura et al, 2002). Conviction subtype TK is characterized by both a strong belief and fear that others will be offended by one's own inadequacies.…”
Section: Introductionmentioning
confidence: 99%